New Balkan records of Bombus subterraneus (Linnaeus 1758) and Bombus cryptarum (Fabricius 1775) from Greece - Anagnostopoulos, Ioannis Th. (ENTOMOLOGIA HELLENICA, 2009)
From the study of the Greek bumblebee fauna (Hymenoptera: Apidae, Bombini), species lists have been published based on both literature records and original data from collected bees. Since 1995 a special effort to confirm with newly collected bees all bumblebee species reported in literature records for Greece has been in progress. Although numerous specimens have been collected and examined and in some instances yielding new Bombus species for the Greek insect fauna, some species, mainly those reported in older references, have not yet been found. Recently, identification of bumblebees collected in the Florina Prefecture - Northwest Macedonia, during the years 2006 and 2007 yielded information for two “literature cited” species, Bombus subterraneus (Linnaeus 1758) and Bombus cryptarum (Fabricius 1775). A B. subterraneus queen (collected at 40°47´38N, 21°26´10E on Vicia cracca) was distinguished by morphological characteristics and a worker B. cryptarum (collected at 40°41´58,7N, 21°28´18,5E on Echium spp) was revealed using mitochondrial DNA RFLP analysis of the CO1 gene. These new records from Florina are provided with comments, confirming the species presence in Greece for the first time after approximately 40 years.